The butterfly (Lepidoptera: Papilionoidea) diversity of Mt. Mosor in Dalmatia, Croatia - Toni Koren; Ivona Burić; Gordana Glavan; Rudi Verovnik (Natura Sloveniae)
Mosor is a small mountain massif situated in central Dalmatia, above the cities of Split and Omiš. It was never a target of any systematic butterfly surveys, with its fauna remaining almost completely unknown. During our surveys from 2011 to 2020, we recorded 96 butterfly species at 60 localities. With the literature record of Polyommatus ripartii, a total of 97 species are recorded from Mt. Mosor. The comparison with the published lists of the neighbouring lower Mt. Kozjak and much higher Mt. Biokovo revealed that the butterfly richness of Mt. Mosor is intermediate, with 87 and 116 species recorded from those mountains, respectively. The biogeographical composition of all three mountains is, however, similar, with the dominant Euro-Siberian and Euro-Oriental faunistic elements comprising together about 80% of the species. For some species with scarce information for Croatia or Dalmatia, like Papilio alexanor, Zerynthia polyxena, Parnassius mnemosynae, Aricia anteros, Polyommatus escheri, Melitaea aurelia, Proterebia phegea, and Neptis rivularis, new records are discussed.